Bronchopulmonary dysplasia as a predictor factor for motor alteration at 6 months corrected age in premature infants Displasia broncopulmonar como fator predisponente para alterações motoras aos 6 meses em prematuros - Priscila Silveira Martins; Rosane Reis de Mello; Kátia Silveira da Silva (Arquivos de Neuro-Psiquiatria, 2010)
OBJECTIVE: The study aimed to assess bronchopulmonary dysplasia (BPD) as a predisposing factor for alteration in the psychomotor development index (PDI) in premature infants and verify the incidence of neuromotor alterations at 6 months corrected age. METHOD: This was a prospective cohort study that followed the neuromotor development of 152 very low birth weight premature infants, with psychomotor development index as the outcome. The study used the Bayley Scale of Infant Development at 6 months corrected age, and neurological examination. RESULTS: Incidence of BPD was 13.2% (n=20). Logistic regression analysis showed an association between BPD and altered psychomotor development index (OR 3.98; 95%CI: 1.04-15.1) after adjusting for confounding variables. Neurological examination was altered in 67.1% of the 152 infants. CONCLUSION: Bronchopulmonary dysplasia acted as an independent predisposing factor for alteration in the psychomotor development index in premature infants at 6 months corrected age. OBJETIVO: Avaliar a displasia broncopulmonar (DBP) como fator predisponente para alteração no índice de desenvolvimento psicomotor em prematuros e verificar a incidência das alterações neuromotoras aos 6 meses de idade corrigida. MéTODO: Estudo de coorte prospectivo que acompanhou o desenvolvimento neuromotor de 152 prematuros de muito baixo peso, cujo desfecho foi o desenvolvimento psicomotor. Utilizou-se a Bayley Scale of Infant Development aos 6 meses de idade corrigida e exame neurológico. RESULTADOS: A incidência de DBP foi de 13,2% (n=20). A análise de regressão logística mostrou associação entre a DBP e alteração no índice de desenvolvimento psicomotor (RC 3,98 IC 95%:1,04-15,1) após ajuste para as variáveis de confundimento. O exame neurológico apresentou-se alterado em 67,1% das 152 crianças. CONCLUSão: A displasia broncopulmonar atuou como fator predisponente independente para alteração no índice de desenvolvimento psicomotor em prematuros aos 6 meses de idade corrigida.